Acoustic emissions and electric signal recordings, when cement mortar beams are subjected to three-point bending under various loading protocols (Fracture and Structural Integrity, 2017)
Two experimental techniques are used study the response of cement mortar beams subjected to three-point bending under various loading protocols. The techniques used are the detection of weak electric current emissions known as Pressure Stimulated Currents and the Acoustic Emissions (in particular, the cumulative AE energy and the b-value analysis). Patterns are detected that can be used to predict upcoming fracture, regardless of the adopted loading protocol in each experiment. The experimental results of the AE and PSC techniques lead to the conclusion that when the calculated Ib values decrease, the PSC starts increasing strongly.
Keywords: Pressure Stimulated Currents; Acoustic Emissions; Cement mortar; Three point bending; b-value